(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study aims to study the effects of sleep on нейропластичностьbrain neuroplasticity. Sleep plays a key role in the renewal and maintenance of nervous system functions. This paper examines the molecular, biochemical, and electrophysiological mechanisms through which sleep affects synaptic connections and brain structures. Various stages of sleep and their specific effects on neural processes, including REM and slow-wave sleep, are discussed. The study highlights the importance of regular sleep to maintain cognitive function, strengthen memory, and prevent neurodegenerative diseases. Special attention is also paid to the interaction between sleep, stress, and brain plasticity, and the effects of chronic sleep deprivation on neuronal structures and functions are investigated. The work is based on data from modern neurophysiological studies, including animal experiments and clinical observations in humans. The results obtained may have important practical implications for the development of new strategies for the treatment and prevention of diseases associated with sleep disorders and нейропластичностьюbrain neuroplasticity.